Climate change and the burden of healthcare financing in African households - Chinwe F. Ezeruigbo; Abel Ezeoha (AOSIS, 2023)
Climate change is a mounting pressure on private health financing in Africa - directly because of increased disease prevalence and indirectly because of its negative impact on household income. The sources and consequences of the pressure constitute an important area of policy discourse, especially as it relates to issues of poverty and inequality. Relying on a panel dataset involving 49 African countries and the period 2000-2019, as well as a random effect regression analysis, this report shows that climate change has a positive and significant impact on the level of out-of-pocket health expenditure (OPHE) in Africa, and an increase in the level of greenhouse (CO2) emissions by 1% could bring about a 0.423% increase in the level of OPHE. Indirectly, the results show that, compared with the regional average, countries that have higher government health expenditure levels, above 1.7% regional average, and face higher climate change risk may likely record an increase in OPHE. Alternatively, countries with higher per capita income (above the regional annual average of $2300.00) are likely to record a drop in OPHE. Countries with lower climate change risk and a lower than the regional average age dependency (above the regional average of 80.4%) are also likely to record a drop in OPHE. It follows that there is a need for policy alignment, especially with regard to how climate change influences primary health care funding models in Africa. Contribution: The results of this research offer policymakers in-depth knowledge of how climate change erodes healthcare financing capacity of government and shifts the burden to households. This raises concerns on the quality of accessible healthcare and the link with poverty and inequality.